Essential PHP tools : modules, extensions, and accelerators - Sklar, David (Expert's voice in open source., 2004)
This book is an essential guide to some of the best free add-ons to PHP. These add-ons, or tools, provide invaluable functionality for improving your PHP web applications, including accessing databases, generating robust Web forms, using page templating systems, creating and parsing XML documents, authenticating users, and much more. In response to the existing shortage of documentation about the tools, author David Sklar packs this book with details about installing, configuring, and using each toolalong with plenty of examples tailored to PHP 4 and 5. Sklar also lays out the details of Auth and HTML_QuickFormtwo hard working PEAR modules, so you don't have to code your own authentication system or Web form construction set! Also included are chapters on debugging programs, and increasing Web server speed. In short, you will learn to eliminate inefficiencies in PHP, and enhance performance without any code modification.